2020
DOI: 10.9734/jeai/2020/v42i730557
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of Cultivated Varieties and Wild Yam Seeds as Efficient Alternative Plant Genetic Resources for Resistant Genotypes against Yam Mosaic Virus (YMV) in Togo

Abstract: In Togo, cultivated yams are severely infected by Yam Mosaic Virus (YMV). In order to find an efficient method for researching genotypes resistant to the virus, this study aims to screen plants obtained from yam seeds. As such, 640 yam seedlings were produced from seeds collected on 20 plants (accessions) of wild yams, D. praehensilis (10) and D. abyssinica (10) and on 12 plants of the complex D. cayenensis-rotundata. The yam seeds were collected during prospections carried out in october 2018, covering 14 dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…From this study, D. praehensilis showed more resistance to the YMV when compared with D. rotundata. This agreed with the study outcomes of [35], who reported high resistance in D. praehensilis in Togo. The high resistance to YMV suggests the existence of resistance genes in the genetic resources of D. praehensilis [35] and which can be exploited in D. rotundata breeding.…”
Section: Path Coefficient Analysis Among Assessed Traits Of D Praehen...supporting
confidence: 91%
“…From this study, D. praehensilis showed more resistance to the YMV when compared with D. rotundata. This agreed with the study outcomes of [35], who reported high resistance in D. praehensilis in Togo. The high resistance to YMV suggests the existence of resistance genes in the genetic resources of D. praehensilis [35] and which can be exploited in D. rotundata breeding.…”
Section: Path Coefficient Analysis Among Assessed Traits Of D Praehen...supporting
confidence: 91%